2015
DOI: 10.1089/ham.2015.0044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Altitude Illness and Use of Pharmacotherapy Among Trekkers and Porters in the Annapurna Region of Nepal

Abstract: We surveyed Nepali porters and guides as well as English- and non-English-speaking trekkers on their knowledge of altitude illness and its treatment during trekking expeditions to the Annapurna region of Nepal. From March 15 to April 15, 2014, Nepali porters and visiting trekkers were surveyed regarding their ability to recognize and treat altitude illness in Manang, Nepal (3540 m). Their personal use of medications and home remedies and presence of acute mountain sickness (AMS) symptoms were also assessed. 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This finding is consistent with the results of a previous survey conducted among trekkers, porters, and guides in the Annapurna region, which showed that all groups lacked knowledge of altitude illness prevention and recognition. 10 In this study, travel by rapid ascent was more common among Nepali patients than among foreigners. Several other reports, including studies of Nepalis on religious pilgrimage to Gosainkunda Lake (4300 m), [11][12][13] have also documented Nepalis ascending rapidly to high altitude, which suggests they are at particular risk of altitude illness.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This finding is consistent with the results of a previous survey conducted among trekkers, porters, and guides in the Annapurna region, which showed that all groups lacked knowledge of altitude illness prevention and recognition. 10 In this study, travel by rapid ascent was more common among Nepali patients than among foreigners. Several other reports, including studies of Nepalis on religious pilgrimage to Gosainkunda Lake (4300 m), [11][12][13] have also documented Nepalis ascending rapidly to high altitude, which suggests they are at particular risk of altitude illness.…”
Section: Discussionmentioning
confidence: 61%
“…This finding is consistent with the results of a previous survey conducted among trekkers, porters, and guides in the Annapurna region, which showed that all groups lacked knowledge of altitude illness prevention and recognition. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation